Persuasive linguistic elements in NYT and NST editorials: discoursal pragmatic interpretive study - Zarza, Sahar; Tan, Helen (Universiti Putra Malaysia Press, 2020)
In positioning the stance of the editorials that play a pivotal role in articulating the official position of the newspaper, the editor needs to have the craft of writing in a credible manner. It is important then that persuasive linguistic elements such as hedges and boosters are utilized in the editorials. Hence, this study aims to adopt a content analysis to investigate the use of hedges and boosters in 240 randomized editorials of The New York Times (NYT: n=120) and New Straits Times (NST: n=120). The results reveal that generally editors use more hedges than boosters. Moreover, interestingly, it was found that NYT editorials tend to use more boosters while the NST editorials exhibit a tendency to hedge more. One possible reason could be the political climate of the time. America being the epitome of democracy provides freedom of speech and this is reflected in the ownerships of newspapers. Unlike Malaysia, owners of NYT newspapers are public individuals and not the government. Therefore, writers of NYT are bold enough to articulate their views without fear or favor. NST editors, in contrast, have to be mindful of what they write as the newspapers are owned by the government of the day.